Embedding Sustainability and Responsibility into the Marketing Curriculum - Onur GUVENC (Communications of International Proceedings, 2022)
Sustainable development continues to become a critical concept for human development and the facilitation of responsibility towards ecosystems while advocating for proper utilization of natural resources and protection of nature. Sustainability and responsibility are essential for social, environmental, and economic development as they create a potential for a better future (Sady et al., 2019). As sustainability is embraced by the United Nations programs, the education sector remains to be the most pivotal element for instilling responsibility among individuals, especially students. That is way in this short review study, we wanted to focus on higher education; especially on marketing education and how sustainability is adapted to the curriculum. In the marketing curriculum, sustainability and responsibility are focused on the development of moral and ethical frameworks for creating modules and learning objectives. The proper incorporation of these concepts into the curriculum lays the path for appropriate learning objectives aimed at resolving ethical and societal challenges linked with sustainability. We believe that this study will help to develop other studies in sustainability and education.
Keywords: Marketing curriculum; case study; sustainability; responsibility